50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3492
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of TeDP Microgrid System Weight and Efficiency to Operating Voltage

Abstract: The development of turboelectric distributed propulsion (TeDP) systems requires the identification of operating voltage standards particular to this revolutionary airborne form of microgrid. This paper introduces a holistic approach for nominal operating voltage and voltage limit definition. Preferred nominal design voltage ranges were identified for the NASA N3-X DC superconducting TeDP system. This was accomplished by decomposing the architecture concept to the subcomponent and device level and integrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…NASA's N3-X design study suggested adoption of a minimum voltage level of 6 kV in order to capture the system level weight reduction benefits [51,128]. In further pursuance, for a cryogenically cooled DC system, a voltage level of 4.5 kV is recommended when optimized for the system mass accounting detailed component mass, efficiency estimations in the system [178]. The SUGAR team design has made a selection for a 10 kV system architecture for the system studies [29,179].…”
Section: High Voltage Architecture and Protectionmentioning
confidence: 99%
“…NASA's N3-X design study suggested adoption of a minimum voltage level of 6 kV in order to capture the system level weight reduction benefits [51,128]. In further pursuance, for a cryogenically cooled DC system, a voltage level of 4.5 kV is recommended when optimized for the system mass accounting detailed component mass, efficiency estimations in the system [178]. The SUGAR team design has made a selection for a 10 kV system architecture for the system studies [29,179].…”
Section: High Voltage Architecture and Protectionmentioning
confidence: 99%
“…It is proposed that the full electrical system is a high temperature superconducting (HTS) cryocooled system, operating at 77K [15] (as far as is technologically possible) to reduce power losses associated with transitioning from an HTS system at 77K, to a warmer non-super conducting system [8]. It is acknowledged that any solid-state switching components within a distributed propulsion electrical architecture are unlikely to be superconducting, and assumed to operate at 100K [8].…”
Section: Tedp Overviewmentioning
confidence: 99%
“…It is acknowledged that any solid-state switching components within a distributed propulsion electrical architecture are unlikely to be superconducting, and assumed to operate at 100K [8]. Clearly the advantages of a superconducting power system must be traded against the mass and efficiency penalties attributable not only to the electrical components of the power system, but also the required cryogenic cooling system.…”
Section: Tedp Overviewmentioning
confidence: 99%
See 2 more Smart Citations